1995
DOI: 10.1116/1.588250
|View full text |Cite
|
Sign up to set email alerts
|

First-order gain-coupled (Ga,In)As/(Al,Ga)As distributed feedback lasers by focused ion beam implantation and insitu overgrowth

Abstract: First-order gain-coupled distributed feedback lasers have been fabricated in the ͑Ga,In͒As/͑Al,Ga͒As material system by maskless patterning with focused ion beam implantation. The laser devices are operating at 77 K and room temperature at emission wavelengths between 1.0 and 0.7 m. The structures obtained are thermally stable up to annealing temperatures of 800°C. A full in situ processing of gain-coupled distributed feedback laser structures was for the first time successfully demonstrated. This process incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In combination with molecular beam epitaxy ͑MBE͒ ultrahigh vacuum ͑UHV͒-type focused ion beam ͑FIB͒ systems may be used for in situ patterning processes. 5 Two main effects can be used in a focused ion beam process to modify the material properties for device applications as it is illustrated in Fig. 1.…”
Section: Of Faceted Samplesmentioning
confidence: 99%
“…In combination with molecular beam epitaxy ͑MBE͒ ultrahigh vacuum ͑UHV͒-type focused ion beam ͑FIB͒ systems may be used for in situ patterning processes. 5 Two main effects can be used in a focused ion beam process to modify the material properties for device applications as it is illustrated in Fig. 1.…”
Section: Of Faceted Samplesmentioning
confidence: 99%
“…The phase mask was produced by FIB implanting a grating pattern into a fused silica sample using a 200 keV Si 2+ beam of 100 nm diameter and subsequently wet etching the sample in a HF solution . Orth et al reported on FIB fabrication of GaInAs/GaAs distributed feedback lasers in a series of articles. Yu et al used FIB implantation with germanium ions to fabricate channel waveguides, grating couplers, Mach–Zehnder interferometers, ring resonators, and directional couplers in silicon …”
Section: Introduction Previous Artmentioning
confidence: 99%
“… 20 Orth et al reported on FIB fabrication of GaInAs/GaAs distributed feedback lasers in a series of articles. 21 23 Yu et al used FIB implantation with germanium ions to fabricate channel waveguides, grating couplers, Mach–Zehnder interferometers, ring resonators, and directional couplers in silicon. 24 …”
Section: Introduction Previous Artmentioning
confidence: 99%